2022
DOI: 10.3389/fendo.2022.922903
|View full text |Cite
|
Sign up to set email alerts
|

Saturation Effect of Body Mass Index on Bone Mineral Density in Adolescents of Different Ages: A Population-Based Study

Abstract: BackgroundAdolescence is a critical period for bone development, and peak bone mass may be reached in late adolescence. Boosting bone accumulation at this time can help preserve adult bone health and avoid osteoporosis later in life. Body mass index (BMI) has been found to have a favorable impact on bone mineral density (BMD) in previous research. However, excessive obesity is harmful to health and may lead to various systemic diseases. Therefore, finding an appropriate BMI to maintain a balance between obesit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
28
0
2

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(30 citation statements)
references
References 49 publications
0
28
0
2
Order By: Relevance
“…Zusammenhänge zwischen den Gewichtsklassen und der Knochendichte werden in der Literatur vielfach aufgezeigt. Knochendichtemessung mittels DXA im Vergleich von Mädchen und Jungen sowie Frauen und Männern zeigen eine signifikante Korrelation von BMI und BMD in den Untersuchungen des National Health and Nutrition Examination Survey (NHANES) [27,28]. In den zitierten Studien wurde sowohl bei Kindern [28] als auch bei Erwachsenen im Alter über 50 Jahre [27] eine Sättigungskurve für die BMD ermittelt.…”
Section: Körpergewicht Knochendichte Und Osteoporoserisikounclassified
See 1 more Smart Citation
“…Zusammenhänge zwischen den Gewichtsklassen und der Knochendichte werden in der Literatur vielfach aufgezeigt. Knochendichtemessung mittels DXA im Vergleich von Mädchen und Jungen sowie Frauen und Männern zeigen eine signifikante Korrelation von BMI und BMD in den Untersuchungen des National Health and Nutrition Examination Survey (NHANES) [27,28]. In den zitierten Studien wurde sowohl bei Kindern [28] als auch bei Erwachsenen im Alter über 50 Jahre [27] eine Sättigungskurve für die BMD ermittelt.…”
Section: Körpergewicht Knochendichte Und Osteoporoserisikounclassified
“…Knochendichtemessung mittels DXA im Vergleich von Mädchen und Jungen sowie Frauen und Männern zeigen eine signifikante Korrelation von BMI und BMD in den Untersuchungen des National Health and Nutrition Examination Survey (NHANES) [27,28]. In den zitierten Studien wurde sowohl bei Kindern [28] als auch bei Erwachsenen im Alter über 50 Jahre [27] eine Sättigungskurve für die BMD ermittelt. Bei den Kindern fiel der Anstieg der BMD pro Anstieg des BMI um einen Punkt im Alter von 8-15 Jahren am höchsten aus und deutlich geringer zwischen 16-19 Jahren.…”
Section: Körpergewicht Knochendichte Und Osteoporoserisikounclassified
“…[ 4 ] Risk factors for bone metabolism in adolescents have received increasing attention from researchers in recent years, and a number of biomarkers and chronic diseases have been shown to be significantly associated with BMD. [ 5 7 ]…”
Section: Introductionmentioning
confidence: 99%
“…[4] Risk factors for bone metabolism in adolescents have received increasing attention from researchers in recent years, and a number of biomarkers and chronic diseases have been shown to be significantly associated with BMD. [5][6][7] Nonalcoholic fatty liver disease (NAFLD) is the most common chronic liver disease and one of the most prevalent chronic diseases, posing a significant global public health burden. More than a quarter of the population in both the United States and Asia now has NAFLD.…”
Section: Introductionmentioning
confidence: 99%
“…To our knowledge, however, existing studies examining the effects of obese status on adolescent BMD and the existence of a saturation effect are insufficient and contentious. Although Yujuan et al (9). concluded that Body mass index (BMI) was positively associated with BMD in adolescents, their study did not adjust for some factors that have been shown to affect BMD in adolescents, such as regulating serum creatinine (10) and uric acid (11), and only considered BMI and did not consider indicators of other obesity conditions, such as waist circumference (WC) and body fat mass.…”
Section: Introductionmentioning
confidence: 99%